Pengaruh Tinkercad sebagai Media Pembelajaran Elektronika Dasar melalui Proyek Digital measuring device - Riskawati; Sri Agustini; Sanusi, Dirgah Kaso (Jurnal Pendidikan Fisika Undiksha, 2024)
This study aims to explore the impact of using Tinkercad and digital measuring tools in basic electronics training for physics students. The training involved 60 students who were given the opportunity to design and test electronic circuits using Tinkercad as a simulation platform and digital measuring tools to measure key parameters in electronics. The analysis of surveys and practical tests showed a significant improvement in students' technical skills, particularly in designing electronic circuits and using digital measuring tools such as multimeters to measure voltage and current. Students' perceptions of the ease of use of Tinkercad and the benefits of digital measuring tools were highly positive, with an average score of 82% for most of the evaluated aspects. These findings support previous research showing that technology-based learning can enhance conceptual understanding and practical skills in electronics education. Overall, the study emphasizes that the integration of digital technologies, such as Tinkercad and digital measuring tools, can make a significant contribution to improving the quality of electronics education and equip students with relevant skills to face challenges in the industrial world.